Factors Associated with the Degree of Dehydration in Toddlers with Diarrhea at Sele Be Solu General Hospital, Sorong City - Hidy L Mayai; Andrew Ivan Humonobe; Claudia A Kurube (Papua Medicine and Health Science, 2026)
Diarrhea remains a major cause of morbidity and mortality among children under five years of age, particularly in low- and middle-income countries, with dehydration representing its most serious complication. This study aimed to analyze factors associated with the degree of dehydration among toddlers with diarrhea at Sele Be Solu General Hospital, Sorong City. An analytic observational study with a cross-sectional design was conducted involving 93 toddlers diagnosed with diarrhea. The independent variables were history of exclusive breastfeeding, family Clean and Healthy Living Behavior (CHLB), parental or caregiver knowledge about diarrhea, child age, and family economic status, while the dependent variable was the degree of dehydration. Data were collected using structured questionnaires and analyzed using the Chi-square test with a significance level of p < 0.05. Exclusive breastfeeding (p = 0.029), parental or caregiver knowledge (p < 0.001), and child age (p < 0.001) were significantly associated with the degree of dehydration. In contrast, family CHLB (p = 0.228) and family economic status (p = 0.343) were not significantly associated. These findings highlight the importance of breastfeeding and caregiver knowledge in relation to dehydration severity among toddlers with diarrhea.